STUDI PENENTUAN STRUKTUR BAWAH PERMUKAAN PADA DAERAH ZONA ALTERASI DENGAN METODE RESISTIVITAS (TAHANAN JENIS) DI KABUPATEN GUNUNG KIDUL D.I YOGYAKARTA - Kaharuddin, Kaharuddin; Said L, Muh.; Rahmaniah, Rahmaniah (Universitas Islam Negeri Alauddin Makassar, 2016)
Research already did by resistivity method (custody species) schlumberger configuration that aim to know of rocks bottom surface structure in alteration zone are district of Gunung Kidul D.I Yogyakarta. Measurement points this research was measured as many as nine sounding points with each disquisition long were 75 m, 100 m and 120 m. the result of interpretation showed that of rocks bottom surface structure in alteration zone area were closed mantle (soil) with resistivity value 9,57 Ωm 14 Ωm on depth (0 – 0,75) m, , clay stone (6,86 – 42,1) Ωm in depth (0 - 9,22) m, sand stone (0,966 – 3,44) Ωm in depth (2,79 – 21,7) m, larva (841 – 1703) Ωm in depth (9,48 - ∞) m. Lava that had alteration was marked by resistivity value which small relative compared with lava which still fresh, this is due to lava which has alteration in area this suspected contain mineral metal so that reisitivity value smaller. lava which had alteration was there in point 1,4 dan 5 with resistivity value 40.5 Ωm – 95.2 Ωm in depth 0 m -∞. While at point 2, 3, 4, 6, 7, 8, 9 there type some structure is: closed mantle (soil), clay stone, sandstone and lava.